Manajemen Sarana Dan Prasarana Pendidikan Anak Berkebutuhan Khusus di Sekolah Luar Biasa Star Kid’s Jember - Siti Syuaibah Faiqotul H; Dani Hermawan; Ahmad Royani (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2022)
Star Kid's Special School is an institution that provides special education services for children with special needs. This institution is located in Kebonsari, Jemer with a total of 26 male and female students with different numbers of disabilities such as the blind, deaf, physically disabled, autistic and multiplely impaired. The Star Kid's Institute has obtained B accreditation, namely through the existence of an educational program that was implemented and managed to get awards and achievements from both the institution and its students. However, there are obstacles in obtaining educational facilities and infrastructure at SLB Star Kid's, such as the difficulty in obtaining facilities and infrastructure to meet the needs of the institution. Therefore this study aims to describe the planning, implementation, and supervision of educational facilities and infrastructure at Star Kid's Special School Jember. This study uses descriptive qualitative methods through the collection of observational data, interviews, and documentation. The results of this study indicate: 1) planning for facilities and infrastructure at the Star Kid's Special School Jember by taking into account the needs analysis and budget analysis which is based on the results of the needs of students' infrastructure that are in accordance with their respective disabilities and will estimate the minimum funds that will be issued. 2) implementation of facilities and infrastructure at Star Kid's Special School Jember which is carried out by forming several teams to carry out implementation processes such as procurement, inventory, distribution, and so on. 3) supervision of facilities and infrastructure carried out directly by the school principal and the team, to directly observe the implementation process at Star Kid's Jember Special School.   Keywords: infrastructure, education, extraordinary school.     Sekolah Luar Biasa Star Kid’s Merupakan lembaga yang memberikan layanan pendidikan khusus untuk ABK. Lembaga ini terletak di kebonsari Jemer dengan jumlah siswa 26 Laki-laki dan  perempuan dengan jumlah ketunaan yang berbeda –beda seperti tuna netra, tuna rungu, tuna daksa, autis dan tuna ganda. Lembaga Star Kid’s telah memperolah akreditasi B yaitu dengan adanya prgram pendidikan yang dilaksanakan dan berhasil mendapatkan penghargaan maupun prestasi baik dari lembaga maupun siswanya. Namun terdapat kendala dalam memperoleh sarana dan prasaranan pendidikan di SLB Star Kid’s seperti sulitnya memperoleh sarana dan prasarana untuk memenuhi kebutuhan lembaga. Oleh karena itu Penelitian ini bertujuan untuk mendeskripsikan perencanaan, implementasi, dan pengawasan sarana  dan prasarana pendidikan di Sekolah Luar Biasa Star Kid’s Jember. Penelitian ini menggunakan metode kualitatif deskriptif melalui pengumpulan data observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan tentang: 1) perencanaan sarana dan prasarana di Sekolah Luar Biasa Star Kid’s Jember dengan memperhatikan analisis kebutuhan dan analisis anggaran yang mana hal tersebut berpegangan pada hasil kebutuhan sarpras siswa yang sesuai dengan ketunaan masing-masing serta akan memperkirakan minim dana yang akan dikeluarkan. 2) implementasi sarana dan prasarana di Sekolah Luar Biasa Star Kid’s Jember yang dilakukan dengan membentuk beberapa tim untuk melaksanakan proses implementasi seperti pengadaan, inventarsasi, distribusi, dan lain sebagainya. 3) pengawasan sarana dan prasarana yang dilakukan langsung oleh kepala sekolah beserta tim, untuk meninjau secara langsung proses implementasi di Sekolah Luar Biasa Star Kid’s Jember. KataKunci:Sarana prasarana, pendidikan, sekolah luar biasa.